Model for the Structure of the Shape-Maintaining Layer of the Escherichia coli Cell Envelope - Braun, Volkmar (1973)
The surface area per repeating murein unit (i.e. per molecule of diaminopimelate) has been determined for the cell envelopes of the Escherichia coli strains K-12 and W. This area was constantly found to be 1.3 nm(2). Using this value and other previously determined properties of E. coli murein, a three-dimensional model of murein is proposed. The model specifies a monomolecular layer in which disaccharide units are each 1.03 nm long, and the polysaccharide chains, all parallel, are 1.25 nm apart. The cross-linking peptide side-chains have the same atomic coordinates and are arranged above or below the polysaccharide chains.